2016
DOI: 10.1007/s00445-016-1074-8
|View full text |Cite
|
Sign up to set email alerts
|

Holocene phreatomagmatic eruptions alongside the densely populated northern shoreline of Lake Kivu, East African Rift: timing and hazard implications

Abstract: The Virunga Volcanic Province (VVP) represents the most active zone of volcanism in the western branch of the East African Rift System. While the VVP's two historically active volcanoes, Nyamulagira and Nyiragongo, have built scoria cones and lava flows in the adjacent lava fields, several small phreatomagmatic eruptive centers lie along Lake Kivu's northern shoreline, highlighting the potential for explosive magma-water interaction. Their presence in the densely urbanized Sake-Goma-Gisenyi area necessitates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…(2020) demonstrate how long‐lake sequences can be used to reconstruct the timing and frequency of volcanism in the East African Rift, an emerging hot‐spot for tephra studies with volcanological, archaeological and palaeoenvironmental focusses (e.g. Poppe et al ., 2016; Campisano et al, 2017; Fontijn et al ., 2018). Martin‐Jones et al .…”
Section: Theme 3: Applications Of Tephrochronology Around the Globementioning
confidence: 99%
See 1 more Smart Citation
“…(2020) demonstrate how long‐lake sequences can be used to reconstruct the timing and frequency of volcanism in the East African Rift, an emerging hot‐spot for tephra studies with volcanological, archaeological and palaeoenvironmental focusses (e.g. Poppe et al ., 2016; Campisano et al, 2017; Fontijn et al ., 2018). Martin‐Jones et al .…”
Section: Theme 3: Applications Of Tephrochronology Around the Globementioning
confidence: 99%
“…Beyond the well-studied European region, Martin-Jones et al (2020) demonstrate how long-lake sequences can be used to reconstruct the timing and frequency of volcanism in the East African Rift, an emerging hot-spot for tephra studies with volcanological, archaeological and palaeoenvironmental focusses (e.g. Poppe et al, 2016;Campisano et al, 2017;Fontijn et al, 2018). Martin-Jones et al (2020) identified nine visible or cryptotephra deposits in sediments from Lake Chala that can be linked to volcanic activity in the Mt Kilamanjaro (Tanzania) and the Chyulu Hills (Kenya) volcanic fields.…”
Section: Theme 1: Tephrochronological Perspectivesmentioning
confidence: 99%
“…They are small, complex, short lived, mainly phreatomagmatic volcanoes that are hazardous for the nearby population (Lorenz 1986(Lorenz , 2007White and Ross 2011;Valentine and White 2012). Around the world, maar-diatremes are found in active monogenetic volcanic fields, some of which are located near large cities such as Auckland, New Zealand (Németh et al 2012;Németh and Kereszturi 2015;Nunns and Hochstein 2019) or Goma, Democratic Republic of Congo (Poppe et al 2016). Maar-diatreme volcanoes comprise a subaerial part composed of an ejecta ring (Self et al 1980;Vazquez and Ort 2006;Valentine et al 2015) and a maar crater (Lorenz 1973;Graettinger 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While there are few data on past volcanism, an increasing number of volcanological, archaeological and palaeoenvironmental studies are beginning to compile and date eruptive deposits preserved both in terrestrial and lake‐sediment sequences throughout East Africa (e.g. Poppe et al, ; Campisano et al , ; Fontijn et al , ; McNamara et al , ). These tephrostratigraphic studies indicate that many volcanoes of the Kenya–Tanzania Rift erupted explosively during the Holocene, depositing ash over hundreds of kilometres (Fontijn et al , ; Martin‐Jones et al, 2017a,b; Lane et al , ; McNamara et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…formed by a single episode of volcanism usually lasting days to weeks, although the more complex polygenetic character of some cones is now being recognised (e.g. Poppe et al , ). The eruption styles and landforms within volcanic fields are often variable: if magma interacts with water, explosive (phreatomagmatic) activity may form maar crater lakes and tuff cones, whereas if low‐viscosity magma is erupted as a fire fountain, spatter cones of welded, ropey lava fragments may develop.…”
Section: Introductionmentioning
confidence: 99%